Energy distribution in cool electrode of electrical discharge machining based on wave-particle dualism. Issue 2 (4th March 2019) - Mingbo, Qiu; Yunxiao, Han; Chao, Zhang; Haoran, Chen; Zhiguang, Hui
Abstract: This paper studies the energy distribution in cool electrode of electrical discharge machining (EDM) on the basis of the wave-particle duality of matter. First, the movement of electrons and ions in the discharge channel was investigated in this article through the wavelength calculation of particles in a discharge channel. The main characteristic of electrons is wave and the moving form is prioritized for diffraction. Ions are mainly characterized by particles. These ions continuously vibrate in the mean free path. Second, a numerical calculation model is proposed on the basis of particle movement. The temperature field in the discharge channel of the cool electrode in the EDM to the titanium alloy is examined using the ANSYS software and simulation result is validated experimentally. Experimental results show that the diameter of the electric corrosion pit on the cool electrode surface is 355 μm, which is less than the electric corrosion pit diameter of 470 μm on a conventional electrode surface. Eventually, the EDM experiment was carried out under the same processing conditions with the cool electrode and the conventional electrode, respectively. The result shows that using cool electrodes in EDM can reduce electrode wear and increase machining efficiency.